2020
DOI: 10.1148/ryct.2020200092
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Disease 2019: Initial Detection on Chest CT in a Retrospective Multicenter Study of 103 Chinese Patients

Abstract: statement: In patients suspected of having COVID-19, the initial chest CT showed high sensitivity, but low specificity. Key Results:(1) The sensitivity, specificity, positive predictive value, and negative predictive value (with 95% confidence intervals) were 93% (85-97%), 53% (27-77%), 92% (83-96%), 42% (18-70%), respectively. Similar results were shown in both geographic regions studied.(2) There were no significant differences in the distribution of positive rates of tests in the two geographic regions betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
130
2
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(147 citation statements)
references
References 16 publications
(21 reference statements)
6
130
2
6
Order By: Relevance
“…Early reports of RT-PCR sensitivity vary considerably, ranging from 42% to 71% (26,27), and an initially negative RT-PCR may take up to 4 days to convert in a patient with COVID-19 (26). The reported sensitivities and specificities of CT for COVID-19 vary widely (60 to 98% and 25% to 53%, respectively) (26)(27)(28)(29), likely due to the retrospective nature of the currently published studies, including lack of strict diagnostic criteria for imaging and procedural differences for confirming infection. The positive and negative predictive value of chest CT for COVID-19 are estimated at 92% and 42%, respectively, in a population with high pretest probability for the disease (e.g., 85% prevalence by RT-PCR) (27).…”
Section: Diagnostic Ct Performance and Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…Early reports of RT-PCR sensitivity vary considerably, ranging from 42% to 71% (26,27), and an initially negative RT-PCR may take up to 4 days to convert in a patient with COVID-19 (26). The reported sensitivities and specificities of CT for COVID-19 vary widely (60 to 98% and 25% to 53%, respectively) (26)(27)(28)(29), likely due to the retrospective nature of the currently published studies, including lack of strict diagnostic criteria for imaging and procedural differences for confirming infection. The positive and negative predictive value of chest CT for COVID-19 are estimated at 92% and 42%, respectively, in a population with high pretest probability for the disease (e.g., 85% prevalence by RT-PCR) (27).…”
Section: Diagnostic Ct Performance and Screeningmentioning
confidence: 99%
“…The reported sensitivities and specificities of CT for COVID-19 vary widely (60 to 98% and 25% to 53%, respectively) (26)(27)(28)(29), likely due to the retrospective nature of the currently published studies, including lack of strict diagnostic criteria for imaging and procedural differences for confirming infection. The positive and negative predictive value of chest CT for COVID-19 are estimated at 92% and 42%, respectively, in a population with high pretest probability for the disease (e.g., 85% prevalence by RT-PCR) (27). The relatively low negative predictive value suggests that CT may not be valuable as a screening test for COVID-19 at least in earlier stages of the disease.…”
Section: Diagnostic Ct Performance and Screeningmentioning
confidence: 99%
“…other types of viral pneumonia), which have the same imaging characteristics of COVID-19 pneumonia [15]. As evidence of this, several studies have demonstrated that the diagnostic performance of chest CT scan shows a wide margin of variability, with high sensitivity (93% [6] and 97% [7]) but with low speci city (53% [6] and 25% [7]) and therefore it is an investigation burdened by the problem of differential diagnosis with other respiratory diseases. Moreover, about half of patients diagnosed with COVID-19 pneumonia may have normal HRTC in the rst two days after onset of symptoms [16].…”
Section: Discussionmentioning
confidence: 97%
“…HRCT has a high sensitivity in detecting lesions (sensitivity range that varies between 93% [6] and 97% [7]) but low speci city (53% [6] and 25% [7]).…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of COVID-19 is essential to limit the spread of the virus and is confirmed by RT-PCR (Reverse Transcriptase Polymerase Chain Reaction) SARS-CoV-2. The sensitivity of the RT-PCR test was evaluated between 42 and 71% [3][4]. Non-contrast chest CT has shown better sensitivity (up to 98%) than RT-PCR for the diagnosis of COVID-19 pneumonia [5].…”
Section: Introductionmentioning
confidence: 99%